An innovative procedure to improve integration algorithm for modified Cam-Clay plasticity model. (August 2020) - Sanei, Manouchehr; Duran, Omar; Devloo, Philippe R.B.; Santos, Erick S.R.
Abstract: An innovative numerical scheme to improve the integration algorithm for critical state elastoplasticity is presented and detailed with special consideration to the modified Cam-Clay model. The scheme is based on a rotation of the principal stresses and represents the elastoplastic model in a rotated Haigh-Westergaard space. Such an approach allows the calculation of modified Cam-Clay tobe computationally stable and easy to implement. The validity of the proposed scheme is verified by comparing the numerical results with analytic solutions.